Resilience to disaster: Evidence from daily wellbeing data - Paul Frijters; David Johnston; Rachel J. Knott; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
As the severity and frequency of natural disasters become more pronounced with climate change and the increased habitation of at-risk areas, it is important to understand people's resilience to them. We quantify resilience by estimating how natural disasters in the US impacted individual wellbeing in a sample of 2.2 million observations, and whether the effect sizes differed by individual- and county-level factors. The event-study design contrasts changes in wellbeing in counties affected by disasters with that of residents in unaffected counties of the same state. We find that people's hedonic wellbeing is reduced by approximately 6% of a standard deviation in the first two weeks following the event, with the effect diminishing rapidly thereafter. The negative effects are driven by White, older, and economically advantaged sub-populations, who exhibit less resilience. We find no evidence that existing indices of community resilience moderate impacts. Our conclusion is that people in the US are, at present, highly resilient to natural disasters.
Keywords: 330